Simple Method for Screening the Affected Birds with Remarkably Hardened Pectoralis Major Muscles among Broiler Chickens - Kawasaki, Takeshi (J Poult Sci, 2016)
Remarkably hardened pectoralis major muscles are increasingly found in broiler chickens in some slaughterhouses in Japan. Based on physical examinations, we selected three affected birds and three control birds from a 43-day-old Ross 308 commercial broiler flock, and examined them biochemically, pathologically, and microbiologically. We found that the presence of degenerative lesions in the pectoralis major muscles was associated with an inability to lift the wings to achieve back-to-back wing contact. As the pectoralis major muscle is a major adductor of the humerus, these degenerative lesions may inhibit the extensibility of the muscle, thereby limiting the range of motion of the humerus. Testing the ability to lift the wing is proposed as a new diagnostic method for detecting affected birds.